(untitled) (Revista Internacional de Formação de Professores, 2024)
Science teaching faces challenges in the prison context, given the uniqueness of this environment. The ongoing training of Science teachers is crucial due to the scarcity of professional development opportunities. The perspectives of a training course for Science teachers in a Penal Complex in the interior of Bahia were analyzed, using the principles of the curricular reconfiguration. The video recordings of the meetings were transcribed and analyzed using Discursive Textual Analysis, from which we obtained an emerging category, namely: Reconfiguring the curriculum in the prison context: promoting social transformations through permanent teacher training. The results highlight a positive vision regarding the implementation of curricular reconfiguration proposals, highlighting the role of the teacher as an agent of change and transformation in the prison environment.